STRATEGI MENGATASI HAMBATAN DALAM MANAJEMEN KELAS UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Nayla Adzkiya Amin; Nida Maulida Ridwana; Nurani Laraswati; Putri Ayu Resfani; Rati Zulkifli; Sofyan Iskandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify challenges in classroom management and formulate effective strategies to improve teaching quality. Using a literature research method, information was gathered from various sources, such as books and relevant scientific journals. The research findings indicate that the main challenges stem from teachers, including overly strict leadership styles, insufficiently varied teaching methods, limited knowledge of classroom management, and a lack of emotional connection with students. Furthermore, classroom layout, media utilization, and time management also contribute to the learning environment. Effective strategies include sound lesson planning, adaptive classroom layout, increased discipline, and positive communication. Appropriate classroom management practices can creat a supportive learning environment, increase student participation, and help achieve optimal learning outcomes.